Security risk analysis and evaluation techniques in power information system cloud - Liang SHEN; Dong WANG; Jiaxing XUAN (Dianxin kexue)
Combining the power industry with cloud computing technology,a systematic study on safety analysis and evaluation methods of the power cloud was carried out.A comprehensive combing on functional entities and business processes of the power information system under the cloud environment was conducted.Through the combination of static STRIDE threat modeling and dynamic attack chain algorithm,the main risks of cloud platform were classified and quantified.A security protection architecture of power cloud system was put forward to promote the popularization and application of cloud computing in the power industry,and to provide a strong support for the safety and control of power information system.